Philippine medical thesaurus on anatomy sense organs and integumentary system - Viola, Chris Elaine S.; Tarlit, Rodolfo Y. (Quezon City Institute of Library and Information Science, University of the Philippines Diliman, 2003)
The University of the Philippines College of Medicine-Philippine General Hospital (UPCM-PGH) is one of the institutions that expressed the need to organize their information resources. Consequently, a construction of a controlled vocabulary was needed to serve as supplement reference and guide material in the field of medicine. This research focused on Sense Organ and Integumentary System subcategories of the 17 subcategories of `Anatomy.' The terms were gathered from the Medical Subject Headings (MeSH) for translation to Tagalog language.
MeSH served as the primary source of medical terms that were translated. Dictionaries from English-Tagalog/Pilipino/Filipino and glossaries were referred in translating the terms. The priority translation tools are those that have been ranked by the experts. Informants such as medical doctors specializing in specific fields such as Otorhinolaryngolgy and others, for instance, "kumadronas", "hilots"... etc. and residence of Bulacan were likewise consulted. At the same time, experts' advice was sought regarding the ambiguity of terms.
While thesaurus construction was a complete task, particularly the translation phase, still the project was able to attain some of it purposes. The researcher ended with 36 translated MeSH terms, 11 terms with definitions and 52 without equivalent terms in Tagalog.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Subject headings, Filipino -- Medicine; Subject headings, Filipino -- Sense organs; Filipino language -- Medical Filipino